Managing environmental challenges: Training as a solution to improve employee green performance. (1st September 2020) - Pham, Nhat Tan; Vo-Thanh, Tan; Shahbaz, Muhammad; Duc Huynh, Toan Luu; Usman, Muhammad
Abstract: Although environmental training program has become a vital solution to minimize environmental challenges, the existing literature has paid little attention to (1) the connection between environmental training and employee in-role green performance (EIGP), (2) the mediating role of employee environmental commitment in this environmental training-EIGP connection, and (3) the cultural perspective (Western and Local) influences on interrelationships between environmental training, EIGP, and employee environmental commitment. Drawing on the social exchange theory and cultural perspective, a quantitative study based on survey data collected from 301 respondents at hotels in Vietnam was employed to fill these research gaps. Findings reveal that environmental training program is as an important tool to drive EIGP directly, and this environmental training-EIGP relationship is significantly mediated by employee environmental commitment. Interestingly, the study indicates support for our prediction that the mediating role of employee environmental commitment on the environmental training-EIGP link is stronger at hotels managed by Western hospitality companies. However, unexpectedly, cultural influence does not moderate the effect of environmental training on EIGP. Other than theoretical contributions, our study carries important practical implications that can help organizations reduce their carbon footprint. Limitations and further research directions have also been discussed. Highlights: Environmental training influences employee in-role green performance (EIGP). Employee environmental commitment mediates the environmental training-EIGP link. The mediating effect is stronger at hotels managed by Western corporations. Cultural influence (Western & Local) does not moderate the environmental training-EIGP link. Our research is the first paper to examine these relationships in the hospitality sector.